2016
DOI: 10.4103/0971-5916.182627
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of vanA gene among vancomycin-resistant enterococci in a tertiary care hospital of North - East India

Abstract: Background & objectives:Vancomycin-resistant enterococci (VRE) have become one of the most challenging nosocomial pathogens with the rapid spread of the multi-drug resistant strain with limited therapeutic options. It is a matter of concern due to its ability to transfer vancomycin resistant gene to other organisms. The present study was undertaken to determine the emergence of vancomycin-resistant enterococci and the vanA gene among the isolates in a tertiary care hospital of North-East India.Methods:A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
(19 reference statements)
2
15
1
Order By: Relevance
“…18 Van A is the most common mechanism for resistance among clinical isolates, so identification of any intermediate susceptibility to vancomycin warrants detailed molecular investigation. 19,20 In this study, Vancomycin intermediate susceptibility was noted among 11 (3.03%) isolates, which is in concordance with other studies. 19,20 Linezolid resistance was detected in 4 (1.10%) Enterococcus isolates, whereas 3(0.82%) isolates demonstrated intermediate susceptibility.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…18 Van A is the most common mechanism for resistance among clinical isolates, so identification of any intermediate susceptibility to vancomycin warrants detailed molecular investigation. 19,20 In this study, Vancomycin intermediate susceptibility was noted among 11 (3.03%) isolates, which is in concordance with other studies. 19,20 Linezolid resistance was detected in 4 (1.10%) Enterococcus isolates, whereas 3(0.82%) isolates demonstrated intermediate susceptibility.…”
Section: Discussionsupporting
confidence: 92%
“…19,20 In this study, Vancomycin intermediate susceptibility was noted among 11 (3.03%) isolates, which is in concordance with other studies. 19,20 Linezolid resistance was detected in 4 (1.10%) Enterococcus isolates, whereas 3(0.82%) isolates demonstrated intermediate susceptibility. Linezolid resistance in Enterococcus has been reported earlier by other researchers also.…”
Section: Discussionsupporting
confidence: 92%
“…Treatment issues for another emerging pathogen, Burkholderia cepacia complex were evaluated in a systematic review (Gautam et al, 2015) Antimicrobial susceptibility data analysis showed a high incidence of resistance among uropathogens (Chatterjee et al, 2016). Antibiograms were a source of information showing rising trend of vancomycinresistant enterococci with nearly 24% isolates demonstrating resistance (Phukan et al, 2016). Importantly, three of the isolates were found to be resistant to linezolid.…”
Section: Prescription Audits and Drug Utilizationmentioning
confidence: 99%
“…In India, the proportion of MRSA pathogen has increased from 29% in 2009 to 47% in 2014, 7 and minimum inhibitory concentration (MIC) of vancomycin is also increasing. 8,9 This necessitates rational use of vancomycin. Pharmacokinetics–pharmacodynamics (PK–PD) assessment and therapeutic drug monitoring (TDM) of vancomycin have been recommended for better clinical outcome and dosing optimization.…”
Section: Introductionmentioning
confidence: 99%